Reproductive History and Cardio-Metabolic Risk in the Postmenopausal Age - Cucinella, Laura; Odone, Anna; Nappi, Rossella E. (Seminars in Reproductive Medicine, 2025)
Menopause represents a cardio-metabolic transition, but cardiovascular (CV) health in women is highly influenced by other reproductive milestones and conditions, which delineate a cardio-reproductive lifeline. Reproductive history represents an opportunity to identify women at elevated risk of CV events after menopause, going beyond traditional CV risk factors. This review aims to summarize the impact of reproductive milestones, gynecological conditions, and pregnancy-related factors on cardio-metabolic health at midlife. The main physio-pathological mechanisms likely implicated in linking reproductive events and CV disease risk are described, as well as the impact of specific conditions (early/late menarche and menstrual dysfunction [functional hypothalamic amenorrhea, polycystic ovary syndrome, benign gynecological conditions (endometriosis, adenomyosis, and fibroids), infertility, adverse pregnancy outcomes, and premature/early natural or surgical menopause]). Data indicate that a reproductive checklist in midlife women is warranted for primary prevention and intervention.
Keywords: menopause; cardiovascular disease; reproductive history; adverse pregnancy outcomes; menstrual dysfunction